2007
DOI: 10.1128/aac.00430-07
|View full text |Cite
|
Sign up to set email alerts
|

Efflux-Related Resistance to Norfloxacin, Dyes, and Biocides in Bloodstream Isolates of Staphylococcus aureus

Abstract: Efflux is an important resistance mechanism in Staphylococcus aureus, but its frequency in patients with bacteremia is unknown. Nonreplicate bloodstream isolates were collected over an 8-month period, and MICs of four common efflux pump substrates, with and without the broad-spectrum efflux pump inhibitor reserpine, were determined (n ‫؍‬ 232).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
160
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(174 citation statements)
references
References 31 publications
13
160
1
Order By: Relevance
“…For example, 1-(1-napthhylmethyl)-piperazine potentiates the effect of tetracycline in A. baumannii, but it increases the resistance of this pathogen to the more clinically relevant antibiotic tigecycline (17). EPIs have contributed substantially to studies of the involvement of efflux pumps in the resistance of clinical isolates (50,125), by demonstrating their ability to reverse resistance. However, a recent study found that reserpine did not accurately predict the overexpression of efflux pumps in Staphylococcus (66).…”
Section: Negating Efflux Pump Activitymentioning
confidence: 99%
“…For example, 1-(1-napthhylmethyl)-piperazine potentiates the effect of tetracycline in A. baumannii, but it increases the resistance of this pathogen to the more clinically relevant antibiotic tigecycline (17). EPIs have contributed substantially to studies of the involvement of efflux pumps in the resistance of clinical isolates (50,125), by demonstrating their ability to reverse resistance. However, a recent study found that reserpine did not accurately predict the overexpression of efflux pumps in Staphylococcus (66).…”
Section: Negating Efflux Pump Activitymentioning
confidence: 99%
“…The role of an MDR efflux-related increase in 301 MIC and skin disinfection with CH is also discussed by DeMarco et al [33]. Efflux mechan-302 isms are also relevant for decreasing susceptibility, for example of Treponema denticola, to 303 hBD-3 [34], although current research findings suggest that MDR efflux pumps do not play 304 an important role in hBD-3-resistance [35].…”
mentioning
confidence: 50%
“…A number of methods have been used to identify the efflux systems in bacteria including use of radio labelled substrates, fluorometric assays or the determination of the MIC in the presence of efflux inhibitors (DeMarco et al, 2007;Patel et al, 2010;Kaatz et al, 2000). In our work from 13 clinical isolates only 8 isolates (61.5%) were found to be NorA and NorB efflux pumps positive.…”
Section: Discussionmentioning
confidence: 75%
“…In our work from 13 clinical isolates only 8 isolates (61.5%) were found to be NorA and NorB efflux pumps positive. A previous work reported 49% prevalence of NorB type efflux pump among S. aureus clinical isolates recovered from blood (DeMarco et al, 2007). Another study also demonstrated occurrence of NorB, MdeA or MepA type efflux pumps in S. aureus (Costa et al, 2011).…”
Section: Discussionmentioning
confidence: 76%